Acute Myocardial Infarction Followed by Cerebral Hemorrhagic Infarction in Polycythemia Vera: Case Report and Literature Review - Shao, XiangSen; Liu, ZhuoTing; Qin, ChunChang; Xiao, Fei (Frontiers in Cardiovascular Medicine, 2021)
A 60-year-old man presented to our emergency room with severe chest pain. Based on the electrocardiogram and elevated serum troponin T levels, acute coronary syndrome was suspected. Coronary angiography revealed total occlusion of the middle of the left anterior descending coronary artery. However, blood cell count abnormalities were not of concern. Twelve days later, the patient developed hemorrhagic infarction in the right parieto-occipital lobe. Acute coronary syndrome and cerebral hemorrhagic infarction were primarily caused by thrombus formation due to polycythemia vera (PV), based on the presence of increased blood consistency on admission. PV was diagnosed after bone marrow biopsy and genetic testing. The patient was treated with descending cell and antiplatelet therapy. Our case highlights the importance of the urgent identification of PV. When acute myocardial infarction occurs in patients with no significant risk factors for cardiovascular disease, blood routine abnormalities should be paid close attention to . If PV was diagnosed as early as possible, thrombotic and hemorrhagic complications could be prevented in the early stages.